EFEKTIVITAS PELATIHAN MANAJEMEN STRES DALAM PENURUNAN STRES KERJA PADA ANGGOTA BADAN SEARCH AND RESCUE NASIONAL (BASARNAS) KOTA PADANG - Mutiara Ramadhani; Widia Sri Ardias (Universitas Muhammadiyah Lampung, 2020)
The purpose of this study was to see what level of stress the work of members of the Padang City BASARNAS before being given training, and after being given stress management training. Furthermore, the research also highlighted the influence of stress management training in reducing work stress on members of the Padang City BASARNAS. The method used in this study is a quantitative method of experimental design with the technique of T-test test analysis with paired sample T-test that is processed with SPSS version 20.0 for Windows. The independent variables in this study were stress management training and work stress dependent variables. The population of this study are members of the Padang City BASARNAS. Using purposive sampling while the data collection techniques in this study use psychological measuring instruments in the form of scales, the scale of work stress totaling 24 items. The results showed that before being given stress management training 4 members of the Padang City BASARNAS had a high stress level category, and 4 people in the moderate category. After being given stress management training the stress level of BASARNAS members in Padang decreased by 5 people in the medium category, and 3 people in the low category. Effective stress management training reduces work stress on members of the Padang City BASARNAS as evidenced by the significant index results of 0,000 (<0.050). Similar training in areas of work with the potential for high levels of work stress is recommended to be carried out so that employee performance can be optimized due to efforts to manage employee stress. Keywords: Training, Stress Management, Job Stress, BASARNAS